Overexpression of a WRKY Transcription Factor TaWRKY2 Enhances Drought Stress Tolerance in Transgenic Wheat - Gao, Huiming; Wang, Yafei; Xu, Ping; Zhang, Zhengbin (Frontiers in plant science, 2018)
Drought is a major environmental stress that severely restricts plant growth and crop productivity. A previous study showed that from wheat ( ) plays an important role in drought stress tolerance. In the present study, we isolated the promoter of and identified multiple regulatory -elements in the promoter region. The activity of the promoter was induced by drought, salt, heat, and abscisic acid (ABA). We also generated -overexpressing transgenic wheat, and found that the transgenic seedlings exhibited significantly enhanced tolerance to drought stress, as evidenced by a higher survival rate and lower water loss rate of detached leaves compared with wild type (WT) plants. In addition, the transgenic lines had higher contents of free proline, soluble sugar, and chlorophyll. During a prolonged period of drought stress before the heading stage, the growth of WT plants was inhibited, whereas the -overexpressing lines progressed to the heading stage. The increased grain yield of the transgenic wheat lines reflected the cumulative effects of longer panicle length, more kernels per spike, and greater aboveground biomass. Our findings show that can enhance drought tolerance and increase grain yield in wheat, thus providing a promising candidate target for improving the drought tolerance of wheat cultivars through genetic engineering.